Computational Prediction of Damaging NSSNPS in PRSS12 gene, Responsible for autosomal recessive non-syndromic mental Retardation. - Hashmi, Bushra Ata; Khan, Muhammad Ayaz; Akhlaq, Muhammad; Khan, Muzammil Ahmad (Journal of Pakistan Psychiatric Society, 2015)
Abstract